Characteristics and Kinetics of Huadian Oil Shale Pyrolysis via Non-isothermal Thermogravimetric and Gray Relational Analysis. Issue 3 (3rd March 2020) - Bai, Fengtian; Sun, Youhong; Liu, Yumin; Guo, Mingyi; Zhao, Jinmin
ABSTRACT: The pyrolysis of Huadian oil shale was carried out in a non-isothermal thermorgravimetric thermal analyzer system. The particle size (0.3–0.45 mm, 0.2–0.3 mm, 0.15–0.2 mm, 0.088–0.15 mm, 0.075–0.088 mm, and <0.075 mm), heating rate (5, 10, 20, and 50℃ min −1 ), and specimen mass (approximately 5 mg, 10 mg, and 15 mg) were considered to study the effects which caused by mass and heat transfer limitations. The kinetic parameters were determined using Kissinger–Akahira–Sunose (KAS), Friedman, and Coats-Redfern method combining the Avrami-Erofeev AE2 kinetic model. And the gray relational analysis method was employed to investigate the influence of particle size, heating rate, and specimen mass on the pyrolysis behavior as well as kinetic parameter. It is showed that, in the second stage, average activation energy of Huadian oil shale was 225 ± 7 KJ mol −1, 240 ± 6.5 KJ mol −1, and 244 ± 21.5 KJ mol −1, calculated by KAS, Friedman, and Coats-Redfern-Avrami-Erofeev method, respectively, indicating that the second stage can be modeled by Avrami-Erofeev AE2 equation. The order of the gray relational grade showed that the particle size, heating rate, and specimen mass exhibit a noticeable relevance to pyrolysis behavior of Huadian oil shale. The heating rate has a significant effect on both the product release rate and average activation energy. The particle size has the least effect on the product release rate, while specimen mass has the least influence on the average activation energy.